Leaching of Phosphomonoesterase Activities in Beech Forest Soils: Consequences for Phosphorus Forms and Mobility - Fetzer, Jasmin; Loeppmann, Sebastian; Frossard, Emmanuel; Manzoor, Aamir; Brödlin, Dominik; Kaiser, Klaus; Hagedorn, Frank (Frontiers in Forests and Global Change, 2021)
Phosphomonoesterases play an important role in soil phosphorus (P) cycle since they hydrolyze P monoester to phosphate. Their activity is generally measured in soil extracts, and thus, it remains uncertain how mobile these enzymes are and to which extent they can be translocated within the soil profile. The presence of phosphomonoesterase in soil solution potentially affects the share of labile dissolved organic P (DOP), which in turn would affect P leaching. Our study aimed at assessing the production and leaching of phosphomonoesterases from organic layers and topsoil horizons in forest soils and its potential effect on dissolved P forms in leachates obtained from zero-tension lysimeters. We measured phosphomonoesterase activities in leached soil solutions and compared it with those in water extracts from litter, Oe/Oa, and A horizons of two beech forests with a contrasting nitrogen (N) and P availability, subjected to experimental N×P fertilization. In addition, we determined phosphate and DOP. In soil solutions leached from litter, Oe/Oa, and A horizons, phosphomonoesterase activities ranged from 2 to 8 µmol L-1 h-1 during summer, but remained below detection limits in winter. The summer values represent 0.1-1% of the phosphomonoesterase activity in soil extracts, indicating that enzymes can be translocated from organic layers and topsoils to greater soil depths. Activities of phosphomonoesterases obtained by water extracts were greater in the organic layer of the P-poor site, while activities of those in soil solutions were similar at the two sites. Nitrogen addition increased phosphomonoesterase activities in leached soil solutions of the organic layer of the N- and P-poor soil. Using a modeling approach, we estimated that approx. 76% of the initial labile DOP was hydrolyzed to dissolved inorganic P (DIP) within the first 24 hours, which represents approx. 15% of total dissolved P. The observed leaching of phosphomonoesterases implies that labile organic P could be hydrolyzed in deeper soil horizons and that extended sample storage leads to an underestimation of the contribution of DOP to total dissolved P leaching. This has been neglected in the few field studies measuring DOP leaching.